2011
DOI: 10.1186/1477-5956-9-1
|View full text |Cite
|
Sign up to set email alerts
|

A proteomic analysis of C-reactive protein stimulated THP-1 monocytes

Abstract: BackgroundC-reactive protein (CRP) is a predictor of cardiovascular risk. It circulates as a pentameric protein in plasma. Recently, a potential dissociation mechanism from the disc-shaped pentameric CRP (pCRP) into single monomers (monomeric or mCRP) has been described. It has been shown that mCRP has strong pro-inflammatory effects on monocytes. To further define the role of mCRP in determining monocyte phenotype, the effects of CRP isoforms on THP-1 protein expression profiles were determined. The hypothesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
51
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(54 citation statements)
references
References 42 publications
3
51
0
Order By: Relevance
“…Total protein of 50 mg-s of crushed B. distachyon inbred line Bd21 seeds were extracted following the protocol of Dupont and co-workers13. Briefly, an SDS-Tris extraction buffer (pH 6.8) containing 2% SDS, 10% glycerol, 50 mM DTT and 40 mM Tris-HCl, pH 6.8 was used to extract the total protein at room temperature for one hour with a regular gentle vortexing.…”
Section: Methodsmentioning
confidence: 99%
“…Total protein of 50 mg-s of crushed B. distachyon inbred line Bd21 seeds were extracted following the protocol of Dupont and co-workers13. Briefly, an SDS-Tris extraction buffer (pH 6.8) containing 2% SDS, 10% glycerol, 50 mM DTT and 40 mM Tris-HCl, pH 6.8 was used to extract the total protein at room temperature for one hour with a regular gentle vortexing.…”
Section: Methodsmentioning
confidence: 99%
“…Mutations in these and other human sHSPs are associated with a wide range of diseases, the majority of which are neuropathies and myopathies (81)(82)(83)(84). Besides possible interactions with elements of the cytoskeleton (85)(86)(87), different members of the chaperone family are found to be present at sites of inflammation (88,89) and cellular defects like ischemic acute renal failure (90) or excitotoxic lesions (91). As a general protective effect, it was reported that high levels of sHSPs extend the life span of some organisms (92)(93)(94).…”
Section: Localization and Physiological Relevancementioning
confidence: 99%
“…Therefore, scientists usually crosslink Igs captured on protein A or G via chemical crosslinkers such as dimethyl pimelimidate (DMP) and bis(sulfosuccinimidyl) suberate (BS3). [162165] However, crosslinkers like DMP may also modify the amine groups on the antigen biding sites, leading to a decrease in antigen binding efficiency. [166] Konrad et.…”
Section: Antibody Immobilization Chemistriesmentioning
confidence: 99%